Data Analytics and Learning Proceedings of DAL 2018 - Nagabhushan, P.; Guru, D. S.; Shekar, B. H.; Kumar, Y. H. Sharath; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents new theories and working models in the area of data analytics and learning. The papers included in this volume were presented at the first International Conference on Data Analytics and Learning (DAL 2018), which was hosted by the Department of Studies in Computer Science, University of Mysore, India on 30-31 March 2018. The areas covered include pattern recognition, image processing, deep learning, computer vision, data analytics, machine learning, artificial intelligence, and intelligent systems. As such, the book offers a valuable resource for researchers and practitioners alike.
Chapter 1: Recognition of 7-Segment Displays from Images of Digital Energy Meters -- Chapter 2: An Enhanced Task Scheduling in Cloud Computing Based on Hybrid Approach -- Chapter 3: A Moment-Based Representation for Online Telugu Handwritten Character Recognition -- Chapter 4: A Switch Prioritized Load Balancing Technique in SDN -- Chapter 5: A Robust Human Gait Recognition Approach Using Multi Interval Features -- Chapter 6: Keyword Spotting in Historical Devanagari Manuscripts by Word Matching -- Chapter 7: A Parallel Programming approach for Estimation of Depth in world co-ordinate system using single camera -- Chapter 8: An Alternate Voltage Controlled Current Source for Electrical Impedance Tomography Applications.
Keywords: Computational intelligence; Data mining; Signal processing; Big data; Computational Intelligence; Data Mining and Knowledge Discovery; Signal, Speech and Image Processing; Big Data